ANALISIS CREDIT SCORING DAN FAKTOR-FAKTOR YANG MEMPENGARUHI NPF PEMBIAYAAN MURABAHAH PADA PT BANK MUAMALAT INDONESIA - Siti Aisyah Nurrizqi Rahmadania; Nurismalatri Nurismalatri (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
Credit scoring is a tool for predicting the financial risk of loan customers and helping banks in analyzing new loans to be provided to customers which is useful for strengthening the credit risk management system. The purpose of this study was to determine how the application of the credit scoring model in mortgage financing or sharia housing in Muamalat banks and to determine the factors that influence murabahah financing Non Performing Financing (NPF). The research method used is descriptive research and quantitative research. The results of the first part of the study indicate that the credit scoring model has become a explanatory variable or potential indicator that has been used by Muamalat banks since 2013 in making mortgage loan decisions. There are 12 assessment parameters based on risk weights in them. The results of the second part of the study show that the rupiah exchange rate has a positive effect on NPF of murabahah financing, while inflation and GDP have no effect on the NPF of murabahah financing